Hygiene, atopy and wheeze–eczema–rhinitis symptoms in schoolchildren from urban and rural Ecuador. Issue 3 (8th October 2013) - Cooper, Philip J; Vaca, Maritza; Rodriguez, Alejandro; Chico, Martha E; Santos, Darci N; Rodrigues, Laura C; Barreto, Mauricio L
Abstract : Background: Rural residence is protective against atopy and wheeze–rhinitis–eczema symptoms in developed countries, an effect attributed to farming and poor hygiene exposures. There are few data from developing countries addressing this question. We compared atopy and wheeze–rhinitis–eczema symptoms between urban and rural Ecuador, and explored the effects of farming and poor hygiene exposures. Methods: We performed cross sectional studies of schoolchildren living in rural and urban Ecuador. Data on symptoms and farming/hygiene exposures were collected by parental questionnaire, atopy by allergen skin prick test reactivity and geohelminth infections by stool examinations. Results: Among 2526 urban and 4295 rural schoolchildren, prevalence was: atopy (10.0% vs 12.5%, p=0.06), wheeze (9.4% vs 10.1%, p=0.05), rhinitis (8.1% vs 6.4%, p=0.02) and eczema (5.9% vs 4.7%, p=0.06). A small proportion of symptoms were attributable to atopy (range 3.9–10.7%) with greater attributable fractions for respiratory symptoms observed in urban schoolchildren. Respiratory symptoms were associated with poor hygiene/farming exposures: wheeze with lack of access to potable water; and rhinitis with household pets, no bathroom facilities and contact with large farm animals. Birth order was inversely associated with respiratory symptoms. Area of residence and atopy had few effects on these associations. Conclusions: Urban schoolchildren living in Ecuador have a similar prevalence of atopy, eczema and wheeze but a higher prevalence of rhinitis compared with rural children. Some farming and poor hygiene exposures were associated with an increase in the prevalence of wheeze or rhinitis while birth order was inversely associated with these symptoms.